Flood Hazard Assessment in Agricultural Areas: The Case of the District of Pélébina in the Municipality of Djougou, Bénin - Sintondji, Luc O.; Dossou-Yovo, Elliott R.; Akogou, Donald; Agbossou, Euloge K. (European Scientific Journal, ESJ, 2017)
Flood is a natural disaster and causes loss of life and property destruction. Its impacts are large on agriculture especially in West African countries where smallholder farmers account for 80% of all the farms. The objective of this study was to assess flood risks in the inland valley of Dosir located in the district of Pélébina, northern Benin. Rainfall, discharge and water level in the riverbed were monitored using rain gauge, acoustic current meter and pressure sensors, respectively. The hydrological functioning of the inland valley was simulated using the Integrated Flood Analysis System (IFAS) model. The calibration was done based on the land use map (GlobalMap) and the soil water holding capacity map (UNEP). Our study demonstrated the existence of a high flood hazard in the inland valley of Dosir which reacts very quickly to rainfall solicitations. The IFAS model has shown a good performance in simulating the runoff in the riverbed of the inland valley with a coefficient of determination of 0.65. The IFAS model can be used to design a flood management system in the district of Pelebina. Further studies are needed to assess the exposure and vulnerability of farmers to flood risk.